Experiences of Hearing Parents of Children with Hearing Loss: A Qualitative Study - Gül Dikeç; Eda Türk; Esin Yüksel; Kübra Çelebi; Meltem Özdemir (MDPI AG, 2023)
This qualitative study was carried out with a phenomenological design to determine the life experiences of the parents of children with hearing loss. The study sample consisted of twenty parents, who did not have hearing loss, of children with hearing loss registered in a special education and rehabilitation center. The data were collected through in-depth interviews in Istanbul between December and January 2022. Colaizzi's phenomenological interpretation method was used for qualitative data analysis. It was determined that parents of children with hearing loss experienced anxiety, sadness, and happiness during diagnosis. They needed more information at first, but then they gained knowledge in the process, and it took work to accept this process. They stated that having a child with hearing loss requires more time, responsibility, and effort than other children. This situation affects their social life, and they experience interpersonal conflicts. When parents were asked how they coped, they said they did it through prayer, social support, or time to themselves. It can be recommended to apply psychosocial intervention programs to the parents of children with hearing loss, especially their mothers, from the first diagnosis process.